The IPASC data format: a consensus data format for photoacoustic imaging - Gröhl, Janek; Hacker, Lina; Cox, Ben T.; Dreher, Kris; Morscher, Stefan; Rakotondrainibe, Avotra; Varray, François; Yip, Lawrence C. M.; Vogt, William C.; Bohndiek, Sarah E. (Photoacoustics, 2022)
Photoacoustic imaging (PAI) is an emerging modality that has shown promise for improving patient management in a range of applications. Unfortunately, the current lack of uniformity in PAI data formats compromises inter-user data exchange and comparison, which impedes: technological progress; effective research collaboration; and efforts to deliver multi-centre clinical trials. To overcome this challenge, the International Photoacoustic Standardisation Consortium (IPASC) has established a data format with a defined consensus metadata structure and developed an open-source software application programming interface (API) to enable conversion from proprietary file formats into the IPASC format. The format is based on Hierarchical Data Format 5 (HDF5) and designed to store photoacoustic raw time series data. Internal quality control mechanisms are included to ensure completeness and consistency of the converted data. By unifying the variety of proprietary data and metadata definitions into a consensus format, IPASC hopes to facilitate the exchange and comparison of PAI data.
Gesehen am 18.05.2022